Psychometrics of Disembodiment and Its Differential Modulation by Visuomotor and Visuotactile Mismatches - Roel Lesur, Marte; Weijs, Marieke Lieve; Simon, Colin; Kannape, Oliver Alan; Lenggenhager, Bigna (iScience, 2020)
Altered states of embodiment are fundamental to the scientific understanding of bodily self consciousness. The feeling of disembodiment during everyday activities is common to clinical conditions; however, the direct study of disembodiment in experimental setups is rare compared to the extensive investigation of illusory embodiment of an external object. Using mixed reality to modulate embodiment through temporally mismatching sensory signals from the own body, we assessed how such mismatches affect phenomenal and physiological aspects of embodiment and measured perceptual thresholds for these across multimodal signals. The results of a principal component analysis suggest that multimodal mismatches generally induce disembodiment by increasing the sense of disownership and deafference and decreasing embodiment; however, this was not generally reflected in physiological changes. Although visual delay decreased embodiment both during active movement and passive touch, the effect was stronger for the former. We discuss the relevance of these findings for understanding bodily self plasticity. [Display omitted] •Temporal multimodal conflict from own body induces disembodiment•Main components of disembodiment are disownership, deafference, and reduced embodiment•Subjective reports are not reflected by implicit measures•Disembodiment increases faster with visuomotor than with visuotactile mismatch Sensory Neuroscience; Cognitive Neuroscience; Applied Sensory Psychophysics